IMPELEMENTASI MANAJEMEN SUPERVISI TEKNOLOGI DI SDN TANAH HABANG KECAMATAN LAMPIHONG KABUPATEN BALANGAN - Ariana Ariana; Syahrani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to describe the implementation of technology supervision improvement management in improving the quality of school-based learning at SDN Tanah Habang, Lampihong District, Balangan Regency, South Kalimantan Province. This research is a qualitative research with a phenomenological approach. The sources of data in this study were obtained through the principal, teachers, education staff, and the community around SDN Tanah Habang, Lampihong District, Balangan Regency. Data collection techniques used are observation, interviews, and documentation. Data processing and analysis techniques through data reduction, data presentation, and verification or drawing conclusions. The results of this study indicate that the management of improving technology supervision in improving the quality of school marching learning at SDN Tanah Habang, Lampihong District, Balangan Regency, South Kalimantan has basically been implemented through involvement of various parties in carrying out activities at the school, but has not gone as expected. This is marked by the lack of discipline on the part of the school and the lack of cooperation with parents of students or the community in implementing school-based quality management.